Rehabilitation management of Pompe disease, from childhood trough adulthood: A systematic review of the literature - Bruno Corrado; Gianluca Ciardi; Clemente Servodio Iammarrone (MDPI AG, 2019)
Pompe disease (PD) is a rare neuromuscular disorder caused by a deficiency of the enzyme acid alpha-glucosidase. There are three forms of PD depending on the age at onset and clinical severity. PD causes involvement of different organ systems, such as the heart, musculoskeletal system, and respiratory system. As of today, enzymere placement therapy represents the main therapeutic tool for PD. Rehabilitation is an integral part of a multidisciplinary approach to this pathology. The goal of the present review is to find scientific evidence for the rehabilitative approach to PD, with respect to both the infantile- and adult-onset forms. A systematic literature review was made using the following databases: Pubmed, Pedro, Cochrane Library, EDS Base Index, Trip, and Cinhal. Randomized controlled trials or cohort studies with a sample population of at least six subjects were retrieved. The PICO method was used to formulate the clinical query. The search resulted in 1665 articles. Of these, four cohort studies were subjected to the final phase of the review. Three studies regarded inspiratory muscle training with a threshold, while the fourth study analyzed the effectiveness of therapeutic, aerobic, and reinforcement exercises. Inspiratory muscle training with a threshold increases the pressures generated during inhalation. Aerobic exercise is capable of increasing patients' muscular endurance and performance. To date, however, rehabilitative treatment for patients with PD has no validation in evidence-based medicine. Further studies, possibly with a larger sample size and higher quality are necessary to confirm the effectiveness of rehabilitation in patients with PD.